Experiences of medical students who are first in family to attend university. Issue 8 (August 2016) - Brosnan, Caragh; Southgate, Erica; Outram, Sue; Lempp, Heidi; Wright, Sarah; Saxby, Troy; Harris, Gillian; Bennett, Anna; Kelly, Brian
Abstract : Context: Students from backgrounds of low socio‐economic status (SES) or who are first in family to attend university (FiF) are under‐represented in medicine. Research has focused on these students' pre‐admission perceptions of medicine, rather than on their lived experience as medical students. Such research is necessary to monitor and understand the potential perpetuation of disadvantage within medical schools. Objectives: This study drew on the theory of Bourdieu to explore FiF students' experiences at one Australian medical school, aiming to identify any barriers faced and inform strategies for equity. Methods: Twenty‐two FiF students were interviewed about their backgrounds, expectations and experiences of medical school. Interviews were recorded, transcribed and analysed thematically. Findings illustrate the influence and interaction of Bourdieu's principal forms of capital (social, economic and cultural) in FiF students' experiences. Results: The absence of health professionals within participants' networks (social capital) was experienced as a barrier to connecting with fellow students and accessing placements. Financial concerns were common among interviewees who juggled paid work with study and worried about expenses associated with the medical programme. Finally, participants' 'medical student' status provided access to new forms of cultural capital, a transition that was received with some ambivalence by participants themselves and their existing social networks. Conclusions: This study revealed the gaps between the forms of capital valued in medical education and those accessible to FiF students. Admitting more students from diverse backgrounds is only one part of the solution; widening participation strategies need to address challenges for FiF students during medical school and should enable students to retain, rather than subdue, their existing, diverse forms of social and cultural capital. Embracing the diversity sought in admissions is likely to benefit student learning, as well as the communities graduates will serve. Change must ideally go beyond medical programmes to address medical culture itself. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss.